2012
DOI: 10.4028/www.scientific.net/amr.450-451.503
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance of Nano Calcium Carbonate Modified Asphalt Concrete AC-13

Abstract: To make nano calcium carbonate as the modifier, firstly the best proportion of nano calcium carbonate is determined as 6% by comparing the influences of different proportions of nano calcium carbonate to the indexes of asphalt. Then the influence of mixing with nano calcium carbonate to the performance of asphalt concrete AC-13 has been studied. Tests show that, the mixing of 6% nano calcium carbonate has improved the dynamic stability of asphalt concrete AC-13 from 991 times/mm to 1269 times/mm; the residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…The density of calcium carbonate is 2.93 g/cm 3 and the melting point is 1339 • C. Some previous studies have indicated the calcium carbonate can also be used as a modifier [17]. Hao found that nanocalcium carbonate could be used as a modifier to improve both the high temperature performance and water stability of asphalt concrete [18].…”
Section: Introductionmentioning
confidence: 99%
“…The density of calcium carbonate is 2.93 g/cm 3 and the melting point is 1339 • C. Some previous studies have indicated the calcium carbonate can also be used as a modifier [17]. Hao found that nanocalcium carbonate could be used as a modifier to improve both the high temperature performance and water stability of asphalt concrete [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of nano-clay can decrease the moisture damage of asphalt mixture [13,18]. A research conducted over nano-CaCO 3 concluded that the dynamic and residual stability of asphalt mixture increased at 6 % nano-CaCO 3 , which infers that both the high-temperature performance and water stability of asphalt mixture gets improved [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mermer, tebeşir ve kalker gibi farklı malzemelerin üretiminde kullanılır. Kalsiyum karbonat, bitümlü bağlayıcıların yüksek sıcaklık performansını ve tekerlek izi dayanımını artırır [9]- [11]. Kalsiyum karbonat kullanımı soyulmaya karşı direnci arttırır ve dolayısıyla nem hassasiyetini azaltır [12].…”
Section: Introductionunclassified